Keterampilan Menulis Wacana Argumentasi Berbahasa Inggris Dengan Metode Esa pada Mahasiswa Level Post Intermediate di STIE Triatma Mulya - Rai Antara, I Made Agung; Sedeng, I Nyoman; Putu Putra, AA (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): March 2016)
This article entitled Writing Skill of English Argumentative Discourse Using Engage, Study, and Activate Method on Post Intermediate Level's Student in STIE Triatma Mulya. The aims of this study are to find out (1) the students competence in writing argumentative discourse and (2) the factors hindered students in witing argumentative discourse. The main theory used in this research is the theory from Brown (2007). The data was collected using observation, interview, documentation, and tes method. The tehniques used were check list, note, and written test.  The result shows that the students’ competence in writing argumentative discourse improved as much as 4,14 %. Some aspects that showed improvements are gramatical cohesive devices, word choice, and mechanic. But, grammar needs to be improved, because this aspect decrease as much as 0, 34 %. The factors hindered students competence in writing argumentative discourse are the types of discourse itself, grammar, and word choice
Keywords: argumentative discourse, engage, study, and activate, grammar, word choice